THE CONSTITUTION OF THE PHILOSOPHY COURSE AT THE CAICÓ CAMPUS OF THE UNIVERSITY OF THE STATE OF RIO GRANDE DO NORTE: AN ANALYSIS FROM THE BEGINNING TO THE PRESENT DAY - de Lima Pacheco, Marcio; de Assis Costa da Silva, Francisco; Chagas Ramos, Rawy (Revista Gênero e Interdisciplinaridade, 2024)
This article aims to show highlight the significanceof the Philosophy Course in the Seridó Region tracing its evolution from inception to the present day. Initially, it addresses the creation of the course, exploring the contexts and motivations for its establishment. Subsequently, the integration of the course within the structure of the State University of Rio Grande do Norte (UERN) and its reception by the institution are discussed. The outcomes achieved by the first class are also evaluated, considering the resulting academic and social impacts. Moreover, the paper examines the current challenges faced by the course. The methodology employed includes a bibliographic approach, supplemented by quantitative and qualitative research methods, providing a detailed and comprehensive analysis.